Unique Presentation of Cerebellopontine Angle Choroid Plexus Papillomas: Case Report and Review of the Literature - Mark Anderson; Parker Babington; Reza Taheri; Mairo Diolombi; Jonathan H. Sherman (Journal of Neurological Surgery Reports, 2014)
Abstract